A study of the bioactive potential of seven neglected and underutilized leaves consumed in Brazil. (1st December 2021) - De Souza, Thais Cristina Lima; Da Silveira, Tayse Ferreira Ferreira; Rodrigues, Maria Isabel; Ruiz, Ana Lucia Tasca Gois; Neves, Daniela Andrade; Duarte, Marta Cristina Teixeira; Cunha-Santos, Elenice Carla Emidio; Kuhnle, Gunter; Ribeiro, Alessandra Braga; Godoy, Helena Teixeira
Highlights: Neglected and underutilized edible species (NUS) are important food sources. Optimization resulted in extracts with promising antioxidant capacities against ROS. O. gratissimum extracts effectively inhibited S . Choleraesuis growth. P. oleracea presented the most promising cytostatic effect against tumor cell lines. O. gratissimum and E. foetidum inhibited nitrosation reaction. Abstract: This study investigated the vitamin C content, total phenolic compounds (TPC), and the potential bioactivities (antioxidant, antiproliferative, antibacterial activities, and inhibition capacity against N -nitrosation) of seven neglected and underutilized species (NUS): culantro ( Eryngium foetidum ), false roselle ( Hibiscus acetosella ), roselle ( Hibiscus sabdariffa ), tree basil ( Ocimum gratissimum ), Barbados Gooseberry ( Pereskia aculeata ), purslane ( Portulaca oleracea ), and tannia ( Xanthosoma sagittifolium ). Phenolic-rich extracts were obtained by a sequential optimization strategy (Plackett-Burman and Central Composite Design). O. gratissimum presented the highest TPC and X. sagittifolium the greater total vitamin C content. Overall, the plant extracts presented promising bioactive capacities, as scavenging capacity against HOCl, H2 O2 and ROO induced oxidation. P. oleracea demonstrated the highest cytostatic effect against ovarian and kidney tumor cells. O. gratissimum effectively inhibited S. Choleraesuis growth. Maximum inhibition on n -nitrosation was showed by O. gratissimum and E. foetidum . These results highlight the studied NUS as sources of potential health-promoting compounds.